Liderazgos políticos y democracia en América latina - Ollier, María Matilde (SocietàMutamentoPolitica, 2018)
Based on an ideal definition of democracy, the article discusses the workings of a low institutionalization pattern as seen in several Latin American countries, which it describes as “pendular democracy”. This kind of democracy is so called as it oscillates between periods of ungovernability and periods of reversal of the rules, each resulting from an extreme style for presidential leadership, either unstable or dominant, respectively. The cases of several South American countries serve the article to show that differences in the workings of said pattern arise from the head of state’s capacity for agency and their governmental resources. Thus, it argues that each kind of leadership is a cause for low democratic institutionalization patterns rather than a consequence of them, as the literature usually states.